2016
DOI: 10.4038/mljsl.v3i2.7324
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patterns of sexual assault among male victims during and after civil strife in Sri Lanka

Abstract: Introduction: After the defeat of terrorism in May 2009, a significant change in the pattern of crime has been observed in Sri Lanka. Further, no in-depth studies have been conducted on male victims of sexual assault. This study was conducted to describe the nature of injuries and characteristics of male victims of sexual assaults during civil strife and compare those with after civil strife. Methods: A cross-sectional study on male victims of sexual assault was conducted at selected tertiary care hospitals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the future, the management process of child sexual abuse should be further improved up to multidisciplinary centres, counseling and victim support. [10] Moreover, organization of institutional case conference (ICC) for the children affected with CSA is an important step for the future development of such multidisciplinary centres. In this research, it was revealed that one fifth of cases were subjected to ICC.…”
Section: P a G E | 38mentioning
confidence: 99%
“…In the future, the management process of child sexual abuse should be further improved up to multidisciplinary centres, counseling and victim support. [10] Moreover, organization of institutional case conference (ICC) for the children affected with CSA is an important step for the future development of such multidisciplinary centres. In this research, it was revealed that one fifth of cases were subjected to ICC.…”
Section: P a G E | 38mentioning
confidence: 99%